2020
DOI: 10.3390/molecules25184178
|View full text |Cite
|
Sign up to set email alerts
|

Extract of Boehmeria nivea Suppresses Mast Cell-Mediated Allergic Inflammation by Inhibiting Mitogen-Activated Protein Kinase and Nuclear Factor-κB

Abstract: Mast cells are effector cells that initiate allergic inflammatory immune responses by inducing inflammatory mediators. Boehmeria nivea (Linn.) Gaudich is a natural herb in the nettle family Urticaceae that possesses numerous pharmacological properties. Despite the various pharmacological benefits of Boehmeria nivea, its effects on allergic inflammation have not yet been determined. Here, we investigated the effect of the ethanol extract of Boehmeria nivea (BNE) on degranulation rat basophilic leukemia (RBL)-2H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…ROS signaling is necessary for mast cell activation (38). NF-kB/MAPK signaling can mediate allergic inflammation promoted by mast cell activation (39). The effect of ROS/MAPK/NF-kB signaling on allergic inflammation merits further study.…”
Section: Discussionmentioning
confidence: 99%
“…ROS signaling is necessary for mast cell activation (38). NF-kB/MAPK signaling can mediate allergic inflammation promoted by mast cell activation (39). The effect of ROS/MAPK/NF-kB signaling on allergic inflammation merits further study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, quercetin is known to ameliorate the pathogenic process of asthma by decreasing IL-4 and IFN-γ synthesis and by regulating Th1/Th2 balance [137]. Recent evidence showed that the administration of polyphenol-rich ethanolic extract of Boehmeria nivea (caffeic acid, catechin, epicatechin, β-sissterol, rutin, luteolin-7glucoside, naringin, hesperidin, chlorogenic acid, and tangeretin) reduces allergic response in mice by suppressing mast cell mediated inflammation, decreasing TNF-α, IL-1β, IL-6, Th2, extracellular-signal-regulated kinase (ERK) and Mitogen-Activated Protein Kinase (MAPK) expression [138]. In murine asthma models, it was found that sesamin (rich in flavonoids) reduced allergic inflammation induce by asthma and airway hyperresponsiveness (AHR), making them an effective adjunct for the treatment of asthma [139].…”
Section: Polyphenols In Allergic Asthma and Rhinitismentioning
confidence: 99%
“…Antihistamines and steroids are effective drugs in the treatment of allergic diseases, but serious side effects hinder their long-term use ( Lim et al, 2020 ). TMDCD is a Chinese herbal compound optimized based on the compound of MXGSD and GuoMinKang, and also is a summary of clinical experience on allergic asthma by professor Wang Qi from Beijing university of Chinese medicine.…”
Section: Introductionmentioning
confidence: 99%